Taxonomic status and typification of the neglected name Calamagrostis vinealis (Poaceae, Agrostidinae) - Paszko, Beata (Phytotaxa, 2021)
The unresolved name Calamagrostis vinealis Steudel (Poaceae, Agrostidinae) is lectotypified and its taxonomic identity is discussed based on the discovery of Baumgarten’s collection at the P herbarium (P02142817), based on which this name was assigned. This collection appears to be a mixed gathering of Calamagrostis epigejos (left-hand specimen) and C. arundinacea (right-hand specimen). Here, the left-hand specimen is designated and labeled as lectotype of the name Calamagrostis vinealis, and in consequence, C. vinealis is a later heterotypic synonym of C. epigejos.